LITHIUM CARBONATE IS NOT BENEFICIAL FOR PATIENTS WITH AMYOTROPHIC LATERAL SCLEROSIS: RESULTS OF THE LICALS TRIAL [EUDRACT NUMBER: 2008-006891-31]. (29th November 2012) - Al-Chalabi, A; Shaw, P; Kelly, J; Morrison, K; Murphy, C; Thornhill, M; Steen, N; Leigh, PN
Abstract : Introduction: A published report of 44 patients with amyotrophic lateral sclerosis (ALS) of whom 16 were randomly selected to take lithium and riluzole and the remainder riluzole alone, suggested a dramatic effect of lithium carbonate on survival. In the group treated with lithium there was 100% survival by the end of the study, 15 months after recruitment, while in the riluzole-only group only 71% survived. Because the trial was small, not double blind or placebo-controlled, we sought to perform a definitive study to test the hypothesis that lithium carbonate improves survival in ALS. Methods: Detailed methods are provided in the published protocol. We used a multi-centre, double blind, randomized, parallel group controlled trial of lithium carbonate (LiCO3) at doses to achieve stable 'therapeutic' plasma levels (0.4–0.8 mmol/l) versus matched placebo in patients with ALS. All patients were on standard ALS treatment of riluzole 100 mg per day. The primary outcome measure was death from any cause at 18 months from the date of randomization. Results: 214 patients were enrolled from 10 centres in England, 107 in each arm. 117 patients (54.7%) were still alive at the study end, 54 on lithium arm and 63 on placebo. The primary outcome showed no difference in survival between groups, either unadjusted (Mantel-Cox log rank χ 2 statistic 1.64, p=0.2) or adjusted for differences between sites (Mantel-Cox Log rank χ 2 statistic 2.11, p=0.147). Conclusion: Lithium carbonate does not improve survival in ALS.